“West” and “East” in the Global Economic System: Facing a New Bipolarity - G. Issayeva; E. Zhussipova; S. Filin; A. Aitymbetova; Z. Bigeldiyeva (Экономика: стратегия и практика, 2022)
The global economic crisis intensifies against the backdrop of inefficient actions of international organizations and individual states. As a result, there is a change in the balance of the world economy. The unipolar economic system is being replaced by a bipolar system that divides the world into the West (USA) and the East (China). In this regard, the problem of economic confrontation between the two powers and smoothing out the imbalance in the world economy due to the collapse of the monopolar world order becomes a relevant problem. This study is devoted to the analysis of the compliance of the Chinese economy with all the characteristics of a leader compared with the US economy. For this purpose, the problem of the competitiveness of the Chinese financial system has been studied. Based on the case study, the development of the Chinese financial market was analyzed in comparison with the US. The main finding is that the role of the Yuan in the international exchange market is insignificant and accounts for 4.3% of the total turnover. In addition, the Yuan is not widely used globally as a reserve currency, although the Yuan has been included in the SDR basket. The general conclusion is that without a freely convertible Yuan and free float, China’s financial system will not be able to compete with the US. Accordingly, China will not be able to become a full-fledged second pole in the global economic system.